UNDERSTANDING THE WORLDVIEW OF ABANGAN PRACTICE: AN ASCETIC CASE IN PETILASAN EYANG SRIGATI AND BRAWIJAYA V AND TAPA KUNGKUM FROM BUMI PERTAPAAN ALAS KETONGGO, NGAWI, EAST JAVA - Mujab, Saiful (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2017)
This project attempts to discover how the worldview of ascetic practice among the Abangans in Ã¢â‚¬Å“Bumi Pertapaan alas Ketonggo-Ngawi-East JavaÃ¢â‚¬Â. This research wants to prove that the worldview of some ascetics maintains that all of their practices in Ketonggo have strong correlation to several spirits, a kind of syncreticism and mysterious realm. The data in this research is collected through participant observation around 5 mounts in two sacral places of Ketonggo forest (Petilasan Brawijaya and Eyang Srigati and Tapa Kungkum in Tempur River). The fi rst phase of the project involves interviewing around 10 pilgrimages who practice the ritual, some native people and central fi gure of Ketonggo forest. This paper concludes that of the ascetic practices both in Petilasan Brawijaya V and Kungkum in Tempur River has strong understanding and correlation to some sacred powers and spirits in the Ketonggo forest. Keywords: Abangan, Ascetic, Kungkum, and Alas Ketonggo